Effect of irrigation, fertiliser type and variety on grain yield and nutritional quality of spelt wheat (Triticum spelta) grown under semi-arid conditions. (1st October 2021) - Wang, Juan; Barański, Marcin; Hasanaliyeva, Gultakin; Korkut, Recep; Kalee, Hassan Ashraa; Leifert, Alice; Winter, Sarah; Janovska, Dagmar; Willson, Adam; Barkla, Bronwyn; Iversen, Per Ole; Seal, Chris; et al.
Highlights: Long-straw varieties had 10–40% higher grain Cu, Fe, Mn and Zn concentrations. The short straw variety Filderstolz had 15–38% higher grain antioxidant activity. Irrigation increased grain yield by 150% but decreased N/crude protein by 11% Irrigation had no substantial effect on the nutritional composition of spelt grain. Use of manure resulted in 18% higher grain yields than mineral NPK. Abstract: Previous studies reported higher antioxidant and mineral micronutrient concentrations in organic compared to conventional wheat flour, but the reasons are poorly understood. Here we report results from a long-term, factorial field experiment designed to assess effects of variety choice, supplementary irrigation and contrasting fertilization regimes used in organic and conventional production on the nutritional quality and yield of spelt wheat grown in a semi-arid environment. Long-straw (Oberkulmer, Rubiota, ZOR) varieties had 10–40% higher grain Cu, Fe, Mn and Zn concentrations, while the modern, short straw variety Filderstolz had 15–38% higher grain antioxidant activity. Supplementary irrigation and the use of manure instead of mineral NPK as fertilizer had no substantial effect on the nutritional composition of spelt grain, but increased grain yields by 150 and 18% respectively. Overall, this suggests that breeding/variety selection is the most promising approach to improve the nutritional quality of spelt grain in semi-arid production environments.